2012
DOI: 10.1002/0471142956.cy0217s62
|View full text |Cite
|
Sign up to set email alerts
|

Super‐Resolution Microscopy: A Comparative Treatment

Abstract: One of the fundamental limitations of optical microscopy is that of diffraction, or in essence, how small a beam of light can be focused by using an optical lens system. This constraint, or barrier if you will, was theoretically described by Ernst Abbe in 1873 and is roughly equal to half the wavelength of light used to probe the system. Many structures, particularly those within cells, are much smaller than this limit and thus are difficult to visualize. Over the last two decades, a new field of super-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 120 publications
(162 reference statements)
0
10
0
Order By: Relevance
“…Because the grid projection is structured on the Z-axis, the optical sectioning resolution is improved two-fold compared with the standard confocal. Therefore, resolutions of 120 nm laterally (XY) and 250 nm axially (Z) can be achieved depending on the wavelength used (Allen et al, 2014;Dan, Yao, & Lei, 2014;Gustafsson, 2000;Gustafsson et al, 2008;Jost & Heintzmann, 2013;Kasuboski, Sigal, Joens, Lillemeier, & Fitzpatrick, 2012;Long et al, 2014).…”
Section: Imaging Pollen Using Superresolution-structured Illuminatimentioning
confidence: 99%
“…Because the grid projection is structured on the Z-axis, the optical sectioning resolution is improved two-fold compared with the standard confocal. Therefore, resolutions of 120 nm laterally (XY) and 250 nm axially (Z) can be achieved depending on the wavelength used (Allen et al, 2014;Dan, Yao, & Lei, 2014;Gustafsson, 2000;Gustafsson et al, 2008;Jost & Heintzmann, 2013;Kasuboski, Sigal, Joens, Lillemeier, & Fitzpatrick, 2012;Long et al, 2014).…”
Section: Imaging Pollen Using Superresolution-structured Illuminatimentioning
confidence: 99%
“…According to Abbe [5] object features separated by less than 0.5λ/NA cannot be resolved, where λ is the free-space wavelength of illumination light and NA is the numerical aperture of the system defined by NA=n×sinθ, where n is the object-space refractive index and θ is the half-angle of the acceptance cone of the objective lens. For conventional white-light microscope systems the Abbe limit is estimated ~250 nm [6].…”
Section: Introductionmentioning
confidence: 99%
“…protocol 1250 | VOL.10 NO.8 | 2015 | nature protocols SR methods. Exhaustive studies comparing SIM with PALM/ STORM, STED and other SR modes can be found in the literature 19,38,39 , and therefore will be only briefly summarized here.Currently, SIM seems to be the best compromise when considering speed, temporal resolution, field of view (FOV) and depth of view, phototoxicity, fluorophore specifications and ease of postacquisition image processing. By principle, SIM is a true WF approach, and therefore temporal imaging is only limited by grid rotations and phase shifts upon acquisition 19 .…”
mentioning
confidence: 99%
“…protocol 1250 | VOL.10 NO.8 | 2015 | nature protocols SR methods. Exhaustive studies comparing SIM with PALM/ STORM, STED and other SR modes can be found in the literature 19,38,39 , and therefore will be only briefly summarized here.…”
mentioning
confidence: 99%